Sex-related health risks and implications for interventions with hospitality women in Hainan, China. - Liao, Su-Su; Schensul, Jean; Wolffers, Ivan (AIDS education and prevention : official publication of the International Society for AIDS Education, 2003)
This article describes the living situations of sex workers (hospitality girls) in a typical rural town in southern China; their personal, social, financial, and psychological needs and expectations; and the social and economic factors that place them at risk for STIs/HIV and unwanted pregnancy, based on the qualitative and quantitative data collected prior to and during a preventive intervention. Though some similarities to knowledge, attitudes, and behaviors of sex workers reported in other Asian countries were identified, this study identified some differences distinctive to the China context, such as how economic factors, kinship, and friendship networks function in the service industry, and how the culture of reproduction and birth control policy interact with and affect sex workers' health and decision-making options. Understanding these factors is critical for design of a culturally and contextually tailored intervention for the reduction of sex-related health risks of women in the sex service industry.
Keywords: Adolescent; Adult; Attitude to Health; China; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Motivation; Pregnancy; Pregnancy, Unwanted; Prostitution; Risk Factors; Rural Population; Sexually Transmitted Diseases